2022
DOI: 10.3390/nu14112343
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intermittent Fasting on Reproductive Hormone Levels in Females and Males: A Review of Human Trials

Abstract: Intermittent fasting is a popular diet for weight loss, but concerns have been raised regarding the effects of fasting on the reproductive health of women and men. Accordingly, we conducted this literature review to clarify the effects of fasting on reproductive hormone levels in humans. Our results suggest that intermittent fasting decreases androgen markers (i.e., testosterone and the free androgen index (FAI)) while increasing sex hormone-binding globulin (SHBG) levels in premenopausal females with obesity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 48 publications
1
32
0
1
Order By: Relevance
“…Research has shown that short-term intermittent fasting can lead to more excellent parasympathetic activity and lower luteal cortisol levels in young women. These results indicate the possibility of producing an anti-stress effect in the luteal phase, which would reduce menstrual symptoms ( 34 , 35 ).…”
Section: Impact Of Dietary Patterns and Macronutrients On Pmsmentioning
confidence: 70%
“…Research has shown that short-term intermittent fasting can lead to more excellent parasympathetic activity and lower luteal cortisol levels in young women. These results indicate the possibility of producing an anti-stress effect in the luteal phase, which would reduce menstrual symptoms ( 34 , 35 ).…”
Section: Impact Of Dietary Patterns and Macronutrients On Pmsmentioning
confidence: 70%
“…31 A recent review focusing on the effects of intermittent fasting on reproductive hormone levels reported the lack of significant effects of fasting on oestrogen, gonadotropins or prolactin levels in women. 32 Further studies must address the potential relationships between intermittent fasting, body fat distribution and sex hormones in healthy and unhealthy women.…”
Section: Effect On Body Weightmentioning
confidence: 99%
“…Studies have shown that IF and TRE have cardiometabolic benefits aligned with the circadian rhythm, independent of their weight loss outcomes. In a symposium review ( 58 ), Cienfuegos and colleagues attributed the cardiometabolic benefits of TRE to circadian rhythm and biological clocks, which affected glucose regulation, beta cell responsiveness, body composition, and body composition body weight, reduction of oxidative stress and metabolic switch ( 24 , 59 62 ). As such, since fasting deprives the body of glucose, and after glycogen stores are depleted (within 12 h of fasting), the energy production is shifted to alternative energy sources such as fatty acids and ketone bodies, leading to the metabolic switch flipping ( 63 ).…”
Section: System Biology Benefits Of If and Trementioning
confidence: 99%